Three-dimensional cross-linking protective coating for lithium metal battery negative electrode and lithium metal battery negative electrode based on three-dimensional cross-linking protective coating

By applying a three-dimensional cross-linking protective coating on the negative electrode of the lithium metal battery, the problems of lithium dendrites and SEI instability are solved, and the higher circulation performance and safety of lithium metal batteries are achieved.

CN119899567AActive Publication Date: 2025-04-29SHAANXI UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411851634.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-29
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Lithium metal batteries face instability of lithium dendrites during the charge and discharge cycle, resulting in the impact of battery safety and service life.

Method used

A three-dimensional cross-linking protective coating is used to form a stable three-dimensional cross-linking network coating by stirring and dissolving materials such as PVA, SBMA, MBA and glycerol at room temperature and drying them in an oven, which is coated on the negative electrode of the lithium metal battery.

Benefits of technology

This three-dimensional cross-linked protective coating significantly enhances the affinity and conductivity of lithium ions, avoids the formation of lithium dendrites, improves the cycling performance and capacity retention of the battery, extends the life of the lithium metal battery, and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899567A_ABST
    Figure CN119899567A_ABST
Patent Text Reader

Abstract

The invention discloses a three-dimensional cross-linking protective coating for a lithium metal battery negative electrode and a lithium metal battery negative electrode based on the three-dimensional cross-linking protective coating, a preparation method of the coating comprises the following steps: dissolving PVA in water, stirring and dissolving, adding glycerol after the solution is cooled to room temperature, and stirring at room temperature to prepare a solution A; adding reaction monomers SBMA and MBA and an initiator into water, stirring and dissolving to obtain a solution B; and adding the solution B into the solution A, and stirring at room temperature to prepare the three-dimensional cross-linking protective coating for the negative electrode of the lithium metal battery. The three-dimensional cross-linked structure protective coating designed and constructed through molecular chain cross-linking has excellent ionic conductivity, high Li < + > transfer number, low resistance and long cycle life, lithium dendrites formed by lithium ions in the electrochemical process are effectively inhibited, and the service life of the lithium metal battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery material development, and relates to a three-dimensional cross-linked protective coating for a lithium metal battery negative electrode and a lithium metal battery negative electrode based thereon. Background Art

[0002] As a key component of the next generation of high energy density battery technology, lithium metal anode has high energy density (3860mA hg -1 ) and low redox potential (-3.04V vs. reference hydrogen electrode), it has attracted widespread attention and application in electric vehicles, portable electronic devices and energy storage systems. However, lithium metal batteries face the following key challenges during the charge and discharge cycle: (1) Formation and growth of lithium dendrites: During the charging process, the deposition of lithium metal is often uneven, resulting in the formation of lithium dendrites. These dendrites will not only continue to grow on the electrode surface, further increasing its volume, but may also penetrate the separator, causing internal short circuits in the battery, thereby causing safety hazards such as fire and explosion. This phenomenon is called the formation of "dead lithium", which seriously affects the safety and service life of the battery. (2) Instability of the solid electrolyte interface (SEI): Lithium metal batteries are prone to form a fragile and uneven solid electrolyte interface (SEI) during the charge and discharge process. The instability of this interface makes it easily damaged during the plating and stripping cycles, resulting in rapid consumption of lithium ions and electrolytes. As the SEI is damaged, the interfacial impedance increases significantly, and the battery's cycling performance and capacity decay rate accelerate, ultimately affecting the overall performance and life of the battery.

[0003] In order to address these challenges, researchers are actively exploring a variety of strategies to improve the performance and safety of lithium metal anodes, including but not limited to: electrolyte formulation optimization; advanced diaphragm material design; application of coating technology; interface engineering. In existing reported patents, such as patent US 5342710A, a poly(2-vinylpyridine) complex is used as a passivation layer, but the interface formed by this method is unstable, and impurities will be introduced to reduce the interface ion conductivity. Patent CN201510005152 uses an in-situ treatment method to form a protective layer of silicon dioxide on the metal surface. The method is simple, but the protective layer is easy to fall off. Patent CN 107123788B uses an organic-inorganic dual protective layer to physically isolate the contact between metal lithium and the electrolyte and prevent the uneven deposition of lithium ions, but the small molecule organic matter used in this method is easy to dissolve and fall off, and the effect is not ideal. Therefore, further efforts are urgently needed to overcome the above challenges of lithium metal batteries and develop a metal lithium negative electrode that can not only achieve uniform lithium deposition, thereby effectively inhibiting the generation of lithium dendrites, but also avoid adverse reactions with the electrolyte during battery operation. This new type of metallic lithium anode should have the following characteristics to ensure its feasibility and safety in practical applications in the field of new energy. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery and a lithium metal battery negative electrode based thereon, thereby solving the technical problems of the growth of lithium dendrites and the limited life of lithium metal batteries in the prior art.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery comprises the following steps:

[0007] S1: PVA is dissolved in water, stirred and dissolved, and after the solution is cooled to room temperature, glycerol is added, and stirred at room temperature to obtain solution A; reaction monomers SBMA and MBA and initiator are added into water, stirred and dissolved, and solution B is obtained;

[0008] S2: adding solution B into solution A and stirring at room temperature to obtain the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery.

[0009] Preferably, PVA is dissolved in water, stirred and dissolved, and glycerol is added after the solution is cooled to room temperature, and stirred at room temperature to obtain solution A, wherein the temperature during stirring and dissolving is 80-120° C. and the time is 0.5-3 h.

[0010] Preferably, in the solution A, the ratio of PVA to water is (0.1-10) g: (10-50) mL; the ratio of PVA to glycerol is (0.1-10) g: (1-5) mL.

[0011] Preferably, the molar ratio of SBMA to MBA is (1-10):1.

[0012] Preferably, the initiator accounts for 1% to 10% of the total mass of SBMA and MBA.

[0013] Preferably, the volume ratio of solution B to solution A is (1-10):(11-55).

[0014] A three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery is prepared by the above method.

[0015] A method for preparing a lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating, comprising coating the above-mentioned three-dimensional cross-linked protective coating for the lithium metal battery negative electrode on one side of an electrode sheet, and then drying it in an oven at 30 to 100° C. for 3 to 12 hours to obtain the lithium metal battery negative electrode containing the three-dimensional cross-linked protective coating.

[0016] A lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating is prepared by the above method.

[0017] A lithium metal battery comprises the above-mentioned lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating; after 300 cycles of discharge at 1C, the lithium metal battery has a capacity of 130-140 mA h / g and a capacity retention rate of 90%-95%.

[0018] Compared with the prior art, the present invention has the following beneficial technical effects:

[0019] The present invention provides a method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery. During the preparation of the coating, a large number of polar functional groups (-OH) are introduced into PVA, which significantly enhances its Li + ion affinity; in addition, the sulfonic acid group and quaternary ammonium group introduced by SBMA construct a conductive path in the three-dimensional cross-linked molecular chain. This structural feature makes the membrane have excellent ionic conductivity and high Li + The number of ion transfers is increased; the introduction of glycerol forms hydrogen bonds, increasing the density of the physical cross-linked network, so that the cross-linked network has higher mechanical strength; this network structure not only has good flexibility, but also can effectively prevent lithium dendrites from piercing the membrane. After the coating is applied on the electrode sheet and thermally polymerized, a three-dimensional cross-linked network coating with a stable structure is formed. Due to the introduction of a large number of polar functional groups (-OH) by PVA, its resistance to Li + The sulfonic acid group and quaternary ammonium group introduced by SBMA construct a conductive path in the three-dimensional cross-linked molecular chain, thereby improving the ionic conductivity, reducing the impedance of the battery during the cycle, and improving the electrochemical performance. The electrode modified by the three-dimensional cross-linked network coating can make lithium ions nucleate uniformly on the electrode surface, thereby effectively inhibiting the formation of lithium ion dendrites in the electrochemical process, and effectively improving the performance and safety of lithium metal batteries.

[0020] Furthermore, PVA is dissolved in water, stirred and dissolved, and glycerol is added after the solution is cooled to room temperature, and stirred at room temperature to obtain solution A, wherein the temperature during stirring and dissolving is 80-120° C. and the time is 0.5-3 h, so that PVA can be quickly dissolved in water to form a clear solution.

[0021] Furthermore, in the solution A, the ratio of PVA to water is (0.1-10) g: (10-50) mL; the ratio of PVA to glycerol is (0.1-10) g: (1-5) mL, which can enhance the three-dimensional cross-linking strength of hydrogen bonds.

[0022] Furthermore, the molar ratio of SBMA to MBA is (1-10):1, which can polymerize into a high molecular polymer containing zwitterions.

[0023] Furthermore, the initiator accounts for 1% to 10% of the total mass of SBMA and MBA, and can cause the monomers to undergo polymerization reaction.

[0024] Furthermore, the volume ratio of solution B to solution A is (1-10):(11-55), which allows the two polymer chains to form three-dimensional crosslinks of physical and chemical bonds.

[0025] In addition, the present invention also discloses a method for preparing a negative electrode of a lithium metal battery containing a three-dimensional cross-linked protective coating, specifically, coating the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery in the present invention on one side of an electrode sheet, and then drying it in an oven at 30 to 100° C. for 3 to 12 hours, so that the three-dimensional cross-linked protective coating can be dried to form a film on the surface of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 Schematic diagram of preparing a PSM film on a bare copper foil in the present invention;

[0028] Figure 2 is the Raman spectrum of the PSM film;

[0029] Figure 3 Figure 2 shows the ionic conductivity of the SS|PSM|SS battery assembled with the PSM membrane prepared in the invention example.

[0030] Figure 4 The charge and discharge curves of the Li@PSM-Cu|LFP battery and the Li@Cu|LFP battery assembled with the Li@PSM-Cu electrode prepared in the example of the invention at constant current densities of 0.2C, 0.5C, 1C, 2C, and 5C respectively;

[0031] Figure 5 Cyclic charge and discharge curves of a Li@PSM-Cu|LFP battery assembled with a Li@PSM-Cu electrode prepared using an example of the present invention and a Li@Cu|LFP battery at a current density of 1C;

[0032] Figure 6 Schematic diagram of the mechanism of the PSM coating in the present invention to avoid lithium dendrites. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0035] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0036] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0038] The present invention provides a method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery, comprising the following steps: S1: dissolving 0.1-10 g of polyvinyl alcohol (PVA) in 10-50 mL of water, stirring at 80-120° C. for 0.5-3 h, and adding 1-5 mL of glycerol after the solution is cooled to room temperature, and stirring at room temperature to obtain a solution A; adding a reaction monomer 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (SBMA) and N,N'-methylenebisacrylamide (MBA) and an initiator (ammonium persulfate, APS) into water, stirring and dissolving to obtain a solution B;

[0039] Wherein, the molar ratio of SBMA to MBA is (1-10):1, and the initiator accounts for 1%-10% of the total mass of SBMA and MBA. The molecular weight of PVA is 75000-150000, and the alcoholysis degree of PVA includes but is not limited to complete alcoholysis (98%-100%) and partial alcoholysis (87%-89%). The water used in this step can be ultrapure water, distilled water or deionized water. Glycerin includes but is not limited to natural glycerin, crude glycerin or refined glycerin.

[0040] S2: adding solution B to solution A, stirring at room temperature for 0.5 to 3 hours, and then ultrasonically treating the mixed system for 0.1 to 1 hour, so that solution A and solution B are mixed more evenly and bubbles formed during stirring are eliminated, thereby preparing the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery. The volume ratio of solution B to solution A is (1 to 10): (11 to 55).

[0041] The present invention also discloses a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery prepared by the above method. At the same time, the present invention also discloses a method for preparing a negative electrode of a lithium metal battery containing a three-dimensional cross-linked protective coating, wherein the three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery is applied to one side of an electrode sheet, and then dried in an oven at 30 to 100°C for 3 to 12 hours, and the obtained electrode sheet is cut into a desired shape to obtain the negative electrode of a lithium metal battery containing a three-dimensional cross-linked protective coating. The thickness of the three-dimensional cross-linked protective coating after drying is 5 μm.

[0042] Preferably, the electrode sheet can be pretreated before being coated with the three-dimensional cross-linked protective coating for the negative electrode of the lithium metal battery. The pretreatment is specifically: washing with water and ethanol 1 to 5 times to remove surface impurities and improve the adhesion of subsequent coatings, and then using a scraper with a thickness range of 10 to 100 μm to coat the three-dimensional cross-linked protective coating for the negative electrode of the lithium metal battery on the cleaned electrode sheet to ensure the uniformity and consistency of the coating. The electrode sheet can be copper foil.

[0043] In the above-mentioned cutting process, the obtained electrode sheet can be punched into a circular electrode sheet with a diameter of 10 to 30 mm, and then assembled into a button battery.

[0044] The present invention also discloses a lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating prepared by the above method. At the same time, the present invention also discloses a lithium metal battery comprising the above lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating, wherein the lithium metal battery has a capacity of 130-140 mA h / g after 300 cycles of discharge at 1C, and a capacity retention rate of 90%-95%.

[0045] The present invention reports a simple strategy for synthesizing a three-dimensional cross-linked network coating with excellent flexibility and ionic conductivity to construct a stable artificial protective layer for lithium metal anodes. Specifically, a zwitterionic polymer molecular chain is formed by free radical polymerization of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (SBMA) and N,N'-methylenebisacrylamide (MBA). Specifically, the sulfonic acid group and quaternary ammonium group introduced by SBMA construct a conductive path in the three-dimensional cross-linked molecular chain. This structural feature makes the membrane have excellent ionic conductivity and high Li + The introduction of polyvinyl alcohol (PVA) and a large number of polar functional groups (-OH) significantly enhanced its Li + ions; glycerol provides hydrogen bonds, increasing the density of the physical cross-linked network, so that the cross-linked network has higher mechanical strength, thereby constructing a three-dimensional cross-linked network artificial solid electrolyte interface (SEI) layer. This network structure improves the affinity of Li + The affinity of Li + It can be uniformly deposited on the electrode surface to form nuclei, effectively avoiding the formation of lithium dendrites. The interface layer has good flexibility and mechanical strength, which can meet the irregular deformation during lithium ion deposition and effectively avoid the piercing of the membrane by lithium dendrites. The three-dimensional cross-linked network coating effectively improves the thermal stability and toughness, so that the electrode surface protective coating of the battery will not decompose easily under high temperature conditions, while reducing the impedance of the battery during the cycle, improving the ionic conductivity, and improving the electrochemical performance, so that the present invention has significant advantages in improving the performance and safety of lithium metal batteries.

[0046] like Figure 6 As shown, the present invention discloses a three-dimensional cross-linked structure protective coating for the negative electrode of a lithium metal battery and a preparation method thereof. The preparation method comprises: dissolving polyvinyl alcohol in water, then mixing the polyvinyl alcohol solution with a small amount of glycerol, and stirring evenly at room temperature. Then, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide and N,N'-methylenebisacrylamide are added to water for dissolution respectively, and after the dissolution is completed, an initiator APS is added to obtain a long polymer chain. The two solutions are stirred and mixed together and ultrasonicated, and then the mixed solution is applied to bare copper with a scraper, and then dried to form a surface protective film, and then punched into a circular electrode sheet. The polyvinyl alcohol in the protective layer introduces a large number of polar functional groups (-OH) to enhance its affinity for Li+ ions, and the sulfonic acid group and quaternary ammonium group introduced into the long polymer chain construct a conductive path in the three-dimensional cross-linked molecular chain. The three-dimensional cross-linked structure protective coating constructed by the molecular chain cross-linking design of the present invention has excellent ionic conductivity and high Li +The high transfer number, low resistance and long cycle life effectively inhibit the formation of lithium dendrites by lithium ions during the electrochemical process and extend the life of lithium metal batteries.

[0047] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to the present application. Conventional instruments and equipment in the art are used in the following examples. The experimental methods for which specific conditions are not indicated in the following examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Various raw materials are used in the following examples, and unless otherwise specified, conventional commercial products are used, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, if not otherwise specified, "%" represents weight percentage, "part" represents weight part, and ratio represents weight ratio.

[0048] Example 1

[0049] A method for preparing a three-dimensional cross-linked structure protective coating for a negative electrode of a lithium metal battery, characterized in that it comprises the following steps:

[0050] Step 1: First, 10 parts of polyvinyl alcohol powder (PVA) (1 g) was dissolved in 150 parts of water (15 mL), heated and stirred at 80°C until dissolved, and then 10 parts of glycerol (Gly) (2 mL) solution was added after the solution was cooled to room temperature, and stirred at room temperature for 1 hour to obtain solution A;

[0051] Step 2: 10 parts of 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt (SBMA) and 0.5 parts of N,N'-methylenebisacrylamide (MBA) are respectively used as reaction monomers, and ammonium persulfate (APS) (accounting for 5 wt% of the monomer weight) is added as an initiator to 20 parts of water solvent, and stirred until all components are dissolved to obtain solution B;

[0052] Step 3: Then add 10 parts of solution B to the above uniform solution A, stir at room temperature for 1 hour, and obtain the three-dimensional cross-linked structure protective coating for the negative electrode of the lithium metal battery.

[0053] Furthermore, the three-dimensional cross-linked structure protective coating for the negative electrode of a lithium metal battery is coated on an electrode sheet and dried to obtain an electrode sheet containing the three-dimensional cross-linked structure protective coating for the negative electrode of a lithium metal battery.

[0054] In this embodiment, the process of preparing the electrode sheet containing the three-dimensional cross-linked structure protective coating of the negative electrode of the lithium metal battery is specifically as follows: a copper foil is attached to a glass sheet with only one side exposed, and washed with water and ethanol; then a scraper is used to apply the three-dimensional cross-linked structure protective coating of the negative electrode of the lithium metal battery on the copper foil after washing with ethanol, and the coating is placed in an oven at 50°C and dried for 5 hours, finally obtaining an electrode sheet containing the three-dimensional cross-linked structure protective coating of the negative electrode of the lithium metal battery, which can be marked as an electrode sheet PSM-Cu.

[0055] Furthermore, in order to verify the excellent effect of the three-dimensional cross-linked protective coating of the negative electrode of the lithium metal battery in the present invention, the following four batteries were assembled and tested, namely Li@PSM-Cu|LFP, Li@Cu|LFP, SS|PSM|SS and SS|PVA|SS.

[0056] The assembly process of the above five batteries is as follows:

[0057] (1) Li@PSM-Cu|LFP (Li@PSM-Cu / diaphragm / lithium iron phosphate) battery:

[0058] The positive electrode of the lithium-ion battery uses a mixture of 50wt% lithium iron phosphate (as an active material), 5wt% binder (polyvinylidene fluoride, PVDF) and 5wt% Ketjen black. After mixing, grind it in a grinder for 1h and then put it into a container. Subsequently, add an appropriate amount of N-methyl-2-pyrrolidone (NMP) as a solvent to the container, and place it on a magnetic stirrer and stir it at a constant speed for 5h to ensure that the mixture reaches a viscous fluid state. In this process, a carbon-coated aluminum foil is used as a current collector, and the mixed slurry is evenly coated on its surface. Then, the carbon-coated aluminum foil coated with the mixture is placed in a vacuum drying oven, the temperature is set to 100°C, and it is taken out for use after 6h of drying. Next, a special slicer is used to cut the prepared carbon-coated aluminum foil coating into several electrode discs to obtain a lithium positive electrode material.

[0059] The negative electrode of the lithium-ion battery is a Li@PSM-Cu electrode, and the positive electrode, negative electrode and PP separator are assembled into an LFP battery, namely Li@PSM-Cu|LFP battery, for subsequent testing.

[0060] The preparation process of Li@PSM-Cu electrode is as follows: Li is deposited on PSM-Cu by electroplating, specifically: PSM-Cu pole piece is used as positive electrode, Li is used as negative electrode, the battery liquid is 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), the solvent is a mixed solution of 1,3-dioxolane (1,3-Dioxolane, DOL) and dimethyl ethylene glycol (Dimethoxyethane, DME), wherein the volume ratio of DOL to DME is 1:1, the amount of LiNO3 added is 2wt%, and the single charging cycle is 10h under the condition of 0.5mAh / h. At this time, Li ions move toward the positive electrode through the diaphragm, and a reduction reaction occurs on the PSM-Cu pole piece, deposited on the surface of the PSM-Cu pole piece, and a 5mAh capacity of Li is formed on the PSM-Cu pole piece. The deposited Li will penetrate the PSM coating film and be pre-deposited on the surface of the copper foil to form a Li@PSM-Cu electrode.

[0061] (2) Li@Cu|LFP (Li@Cu / diaphragm / lithium iron phosphate) battery:

[0062] The positive electrode of the lithium-ion battery is Li@Cu, and the negative electrode is lithium iron phosphate; the Li@Cu electrode is lithium deposited on the surface of the conductive foil.

[0063] (3) SS|PSM|SS (SS / PSM / SS) battery:

[0064] The positive and negative electrodes of the lithium-ion battery are both gaskets (SS), and the positive electrode, negative electrode and PSM membrane are assembled into a SS|PSM|SS battery for subsequent testing. The PSM membrane is used as a separator.

[0065] The preparation process of the above-mentioned PSM membrane is as follows: pouring the slurry, namely the precursor C solution, onto a polytetrafluoroethylene plate and drying it to form a film, which is then peeled off and cut into the size of a battery separator.

[0066] (4) SS|PVA|SS (SS / PVA / SS) battery:

[0067] The positive and negative electrodes of the lithium-ion battery are both gaskets (SS), and the positive electrode, negative electrode and PVA film are assembled into SS|PVA|SS battery for subsequent testing. PVA film is used as a separator.

[0068] Figure 1This is a schematic diagram of preparing a PSM film on a bare copper foil in the present invention. As can be seen from the figure, a rigid PVA cluster is used to construct the first network, and SBMA and MBA monomers are free radical polymerized to construct the second network, namely P(SBMA-MBA). Here, P(SBMA-MBA) can be used as a soft network, and the hydroxyl group of Gly can interact with the functional groups of the PVA and P(SBMA-MBA) molecular chains through hydrogen bonds to enhance the physical cross-linking network of the coating. In this process, due to the addition of an initiator, a polymerization reaction is initiated during the drying process of the coating.

[0069] Figure 2 This is the Raman spectrum of the PSM film prepared in the present invention. It can be seen from the figure that S=O at 1039cm -1 and -N + (CH 3 ) 2 At 2978cm -1 The stretching vibration of OH, which is a sign of electrostatic interaction, is between 3422 and 3467 cm -1 The results showed that there were hydrogen bonds and electrostatic interactions in PSM, and the cross-linked network coating was successfully synthesized.

[0070] Figure 3 The impedance test results of the SS|PSM|SS battery and the SS|PVA|SS battery in the present invention are shown in the figure. The ionic conductivity in the battery is calculated using the impedance test results in the figure. As can be seen from the figure, due to the interaction between ions and dipoles, the ionic conductivity in the battery with PSM as the separator is 1.14×10 -4 Scm -1 , which is much higher than the ionic conductivity of 0.42×10 -4 Scm -1 .

[0071] Figure 4 The charge and discharge curves of the Li@PSM-Cu|LFP battery and the Li@Cu|LFP battery assembled with the Li@PSM-Cu electrode prepared in the example of the invention at constant current densities of 0.2C, 0.5C, 1C, 2C, and 5C, respectively. It can be seen from the figure that at 1C (1C = 170mA g -1 ) After 120 cycles under the same conditions, the initial capacity of Li@Cu|LFP was 135.1mA h / g, which dropped sharply and the battery began to fail gradually. The initial discharge capacity of the Li@PSM-Cu|LFP full battery was 139.3mA h / g, and after 300 stable discharges, the capacity dropped to 133.5mA h / g, with a capacity retention rate of 93.8%, and a significant improvement in cycle performance.

[0072] Figure 5The cyclic charge and discharge curves of the Li@PSM-Cu|LFP battery assembled with the Li@PSM-Cu electrode prepared by the invention example and the Li@Cu|LFP battery at a current density of 1C. It can be seen from the figure that at current densities of 0.2, 0.5, 1, 2 and 5C, the discharge capacity of the fully charged Li@PSM-Cu|LFP battery is always much higher than that of the Li@Cu|LFP battery, which means that PSM can significantly improve the utilization rate of LFP.

[0073] The present invention discloses a three-dimensional cross-linked structure protective coating for the negative electrode of a lithium metal battery and a preparation method thereof. The preparation method comprises: dissolving polyvinyl alcohol in water, then mixing the polyvinyl alcohol solution with a small amount of glycerol, and stirring evenly at room temperature. Then, [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide and N,N'-methylenebisacrylamide are added to water for dissolution respectively, and after the dissolution is completed, an initiator APS is added to obtain a long polymer chain. The two solutions are stirred and mixed together and ultrasonicated, and then the mixed solution is applied to bare copper with a scraper, and then dried to form a surface protective film, and then punched into a circular electrode sheet. The polyvinyl alcohol in the protective layer introduces a large number of polar functional groups (-OH) to enhance its affinity for Li+ ions, and the sulfonic acid group and quaternary ammonium group introduced into the long polymer chain construct a conductive path in the three-dimensional cross-linked molecular chain. The three-dimensional cross-linked structure protective coating constructed by the molecular chain cross-linking design of the present invention has excellent ionic conductivity and high Li + The high transfer number, low resistance and long cycle life effectively inhibit the formation of lithium dendrites by lithium ions during the electrochemical process and extend the life of lithium metal batteries.

[0074] Example 2

[0075] A method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery comprises the following steps:

[0076] S1: 0.1 g of PVA was dissolved in 10 mL of water, stirred at 80 °C for 3 h, and after the solution was cooled to room temperature, 1 mL of glycerol was added and stirred at room temperature to obtain solution A; reaction monomers SBMA, MBA and APS were added to water, stirred and dissolved to obtain solution B;

[0077] The molar ratio of SBMA to MBA is 1:1, and the initiator accounts for 1% of the total mass of SBMA and MBA.

[0078] S2: Add solution B to solution A, stir at room temperature for 0.5 h, and then ultrasonically treat the mixed system for 0.1 h, so that solution A and solution B are mixed more evenly and bubbles formed during stirring are eliminated, thereby preparing the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery. The volume ratio of solution B to solution A is 1:11.

[0079] In this embodiment, the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery prepared above is applied to one side of an electrode sheet, and then dried in an oven at 30°C for 12 hours, and the obtained electrode sheet is cut into a desired shape to obtain the negative electrode of a lithium metal battery containing the three-dimensional cross-linked protective coating. The thickness of the three-dimensional cross-linked protective coating after drying is 5 μm. The negative electrode of the lithium metal battery is cut and assembled into a lithium metal battery. After 300 cycles of discharge at 1C, the capacity of the lithium metal battery is 130 mA h / g, and the capacity retention rate is 90%.

[0080] Example 3

[0081] A method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery comprises the following steps:

[0082] S1: Dissolve 10 g of PVA in 50 mL of water, stir at 120 °C for 0.5 h, and add 5 mL of glycerol after the solution is cooled to room temperature, and stir at room temperature to obtain solution A; add the reaction monomers SBMA, MBA and APS into water, stir and dissolve to obtain solution B;

[0083] The molar ratio of SBMA to MBA is 10:1, and the initiator accounts for 10% of the total mass of SBMA and MBA.

[0084] S2: Add solution B to solution A, stir at room temperature for 3 hours, and then ultrasonically treat the mixed system for 1 hour, so that solution A and solution B are mixed more evenly and bubbles formed during stirring are eliminated, thereby preparing the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery. The volume ratio of solution B to solution A is 10:55.

[0085] In this embodiment, the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery prepared above is applied to one side of an electrode sheet, and then dried in an oven at 100°C for 3 hours, and the obtained electrode sheet is cut into a desired shape to obtain the negative electrode of a lithium metal battery containing the three-dimensional cross-linked protective coating. The thickness of the three-dimensional cross-linked protective coating after drying is 5 μm. The negative electrode of the lithium metal battery is cut and assembled into a lithium metal battery. After 300 cycles of discharge at 1C, the capacity of the lithium metal battery is 141 mA h / g, and the capacity retention rate is 94.8%.

[0086] Example 4

[0087] A method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery comprises the following steps:

[0088] S1: Dissolve 5 g of PVA in 25 mL of water, stir at 100 °C for 2 h, and add 2 mL of glycerol after the solution is cooled to room temperature, and stir at room temperature to obtain solution A; add the reaction monomers SBMA, MBA and APS into water, stir and dissolve to obtain solution B;

[0089] The molar ratio of SBMA to MBA is 5:1, and the initiator accounts for 5% of the total mass of SBMA and MBA.

[0090] S2: Add solution B to solution A, stir at room temperature for 2 hours, and then ultrasonically treat the mixed system for 0.5 hours, so that solution A and solution B are mixed more evenly and bubbles formed during stirring are eliminated, thereby preparing the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery. The volume ratio of solution B to solution A is 5:20.

[0091] In this embodiment, the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery prepared above is applied to one side of an electrode sheet, and then dried in an oven at 70°C for 10 hours, and the obtained electrode sheet is cut into a desired shape to obtain the negative electrode of a lithium metal battery containing the three-dimensional cross-linked protective coating. The thickness of the three-dimensional cross-linked protective coating after drying is 5 μm. The negative electrode of the lithium metal battery is cut and assembled into a lithium metal battery. After 300 cycles of discharge at 1C, the capacity of the lithium metal battery is 133 mA h / g, and the capacity retention rate is 92.5%.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery, characterized in that: The following steps are involved: S1: PVA is dissolved in water, stirred and dissolved, and after the solution is cooled to room temperature, glycerol is added, and stirred at room temperature to obtain solution A; reaction monomers SBMA and MBA and initiator are added into water, stirred and dissolved, and solution B is obtained; S2: adding solution B into solution A and stirring at room temperature to obtain the three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery.

2. The method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery according to claim 1, characterized in that: The PVA is dissolved in water, stirred and dissolved, and after the solution is cooled to room temperature, glycerol is added and stirred at room temperature to obtain solution A, wherein the temperature during stirring and dissolving is 80-120° C. and the time is 0.5-3 h.

3. The method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery according to claim 1, characterized in that: In the solution A, the ratio of PVA to water is (0.1-10) g: (10-50) mL; the ratio of PVA to glycerol is (0.1-10) g: (1-5) mL.

4. The method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery according to claim 1, characterized in that: The molar ratio of SBMA to MBA is (1-10):

1.

5. The method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery according to claim 1, characterized in that: The initiator accounts for 1% to 10% of the total mass of SBMA and MBA.

6. The method for preparing a three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery according to claim 1, characterized in that: The volume ratio of solution B to solution A is (1-10):(11-55).

7. A three-dimensional cross-linked protective coating for a negative electrode of a lithium metal battery, characterized in that: Prepared by the method according to any one of claims 1 to 6.

8. A method for preparing a lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating, characterized in that: The three-dimensional cross-linked protective coating for the negative electrode of a lithium metal battery as described in claim 7 is applied to one side of the electrode sheet, and then dried in an oven at 30-100° C. for 3-12 h to obtain the negative electrode of a lithium metal battery containing the three-dimensional cross-linked protective coating.

9. A lithium metal battery negative electrode containing a three-dimensional cross-linked protective coating, characterized in that: Prepared by the method of claim 8.

10. A lithium metal battery, characterized in that: A lithium metal battery negative electrode comprising a three-dimensional cross-linked protective coating as described in claim 9; after 300 cycles of discharge at 1C, the lithium metal battery has a capacity of 130-140 mA h / g and a capacity retention rate of 90%-95%.

Citation Information

Patent Citations

  • Method for protective treatment of lithium cathodes in lithium secondary batteries

    CN104617259A

  • A lithium metal anode with a dual organic-inorganic protective layer

    CN107123788B

  • Lakyer for stabilization of lithium anode

    US5342710A

  • Lithium metal battery

    CN106159313A

  • Secondary battery, apparatus comprising secondary battery, preparation method for secondary battery, and adhesive composition

    CN113273005A